The criminal poetics of the detecting body in Gillian Flynn's Sharp objects - Szarvas Réka; Flynn Gillian (SZTE IEAS Szeged, 2024)
Domestic noir, a 21st -century subgenre of crime fiction is famous for its subversive take on seemingly safe and comforting concepts: it discloses the home and the family as socio-cultural and spatial arrangements hiding dangerous prospects for its inhabitants, especially unsuspecting heroines. The primarily female-authored genre – a descendant of the female gothic – often highlights the toxic nature of societal expectations prescribed by conservative patriarchal models of femininity. Focusing on Gillian Flynn’s debut novel, Sharp Objects, I wish to argue that the amateur detective anti-heroine Camille’s self-cutting can be interpreted as an embodied means of feminine writing against domestic entrapment. The diary she carves into her flesh resonates with French feminist theorists’ écriture féminine, while it also functions as a compensatory means of communicating repressed psychic contents. It is a way to cope with trauma through the performative storytelling of self-mutilation that traces signs for the detective and the reader to decode.
Keywords: Bölcsészettudományok; Nyelvek és irodalom